Focal cryoablation of atrioventricular node reentrant tachycardia: a review and comparison of data. (January 2021) - Tomaiko, Emrie; Liao, Ying-Chieh; Reichert, William B.; Su, Wilber W.
Abstract : Purpose of review: Atrioventricular node reentrant tachycardia (AVNRT) is the most common mechanism of supraventricular tachycardia. Radiofrequency ablation has been the most prevalent method for slow pathway ablation but carries risk of atrioventricular node injury. Focal cryoablation has been utilized as an alternative ablation modality; however, there has been concern about decreased efficacy, resulting in a higher rate of recurrence postablation. We also report outcomes from two international centers using an 8-mm cryocatheter and complete a thorough comparison of existing data on ablation of AVNRT. Recent findings: Previous reviews included studies from 2006 onward. These studies included use of the 4 mm focal cryocatheter, which has largely been abandoned in current adult practice. We will cite more contemporary studies within the past 10 years, which also includes use of the 6 and 8 mm cryocatheter. Summary: The use of focal cryoablation allows for reversible injury during AVNRT ablation, providing safety from permanent atrioventricular node injury. With the appropriate ablation endpoints, 8 mm focal cryoablation is more effective for permanent lesion formation, leading to lower recurrences.